Enhanced bone formation by strontium modified calcium sulfate hemihydrate in ovariectomized rat critical-size calvarial defects. (5th June 2017) - Yang, Shenyu; Wang, Lei; Feng, Shanbao; Yang, Qinmeng; Yu, Bin; Tu, Mei
Abstract: The development of a new generation of biomaterials with high osteogenic ability for treatment of osteoporotic fractures is being intensively investigated. The objective of this paper was to investigate new bone formation in an ovariectomized rat (OVX rat) calvarial model of critical size bone defects filled with Sr-containing α -calcium sulfate hemihydrate (SrCSH) cement compared to an α -calcium sulfate hemihydrate ( α -CSH) cement and empty defect. X-ray diffraction analysis verified the partial substitution of Sr 2+ for Ca 2+ did not change the phase composition of α -CSH. Scanning electron microscopy showed that Sr-substituted α -CSH significantly increased the surface roughness. The effects of Sr substitution on the biological properties of SrCSH cement were evaluated by adhesion, proliferation, alkaline phosphatase (ALP) activity of osteoblast-like cells MC3T3-E1. The results showed that SrCSHs enhanced MC3T3-E1 cell proliferation, differentiation, and ALP activity. Furthermore, SrCSH cement was used to repair critical-sized OVX rat calvarial defects. The in vivo results revealed that SrCSH had good osteogenic capability and stimulated new blood vessel formation in a critical sized OVX calvarial defect within 12 weeks, suggesting that SrCSH cement has more potential for application in bone tissue regeneration.